THE INFLUENCE OF RISK PERCEPTION, RETURN EXPECTATIONS, BEHAVIORAL MOTIVATION AND TECHNOLOGICAL PROGRESS ON INVESTMENT DECISIONS IN ISLAMIC PEER TO PEER FINTECH - Maulana Abdul Malik Tambunan; Nurbaiti Nurbaiti; Muhammad Lathief Ilhamy Nasution (SEAN Institute, 2023)
This study aims to determine the extent of the influence of Risk Perception (X1), Return Expectation (X2), Behavioral Motivation (X3), and Technological Progress (X4) on Investment Decisions (Y). This study uses a quantitative approach with sampling using the non-probability sampling method. The type of data used in this study is Primary Data obtained from questionnaires filled out by respondents directly. While secondary data comes from books, journals, research results, practical work reports and is related to the author's research object. In this study, the population to be taken is investors or lenders who invest in Islamic peer to peer fintech domiciled in North Sumatra in 2022 as many as 430 people with a sample selection using the slovin formula of 81 people. The analysis tool uses multiple linear regression analysis. The results showed that Risk Perception (X1), Return Expectation (X2), Behavioral Motivation (X3), and Technological Progress (X4) simultaneously influenced the Investment Decision (Y). The coefficient of determination is 0.741. This means that 74.1% of Investment Decisions (Y) are influenced by Risk Perception (X1), Return Expectation (X2), Behavioral Motivation (X3), and Technological Progress (X4) while the remaining 25.9% is influenced by other variables not examined in this study.